Korean Immigrant Women's Postpartum Experiences in the United States. Issue 1 (January 2020) - Han, Meekyung; Goyal, Deepika; Lee, Jiyoung; Cho, Hyang; Kim, Amber
Abstract: Background: Postpartum depression (PPD) affects one in seven women in the United States. Korean Americans are one of the six largest Asian American (AA) subgroups, representing 9% of the AA population in the United States. Women of Asian descent have not always been represented in studies of PPD. Purpose: The purpose of this study was to understand postpartum experiences, perceptions of PPD, and mental health help-seeking among Korean women living in the United States. Methods: Individual, face-to-face, semistructured interviews of Korean immigrant women, over age 18, who were able to read, write, and speak English or Korean, and who had given birth to a live infant within the past 12 months, were conducted using a qualitative exploratory design. Thematic analysis approach was used to analyze qualitative data The Edinburgh Postnatal Depression Screening Scale (EPDS) was used to assess frequency of depressive symptoms over the past week. Results: Eleven women participated. Total EPDS scores ranged from 2 to 17 (mean 6.5, SD = 3.2); three women had scores indicating a high risk for developing PPD. Two overall themes, postpartum experiences and perceptions of PPD and professional help-seeking, along with several subthemes were identified. They included postpartum challenges, importance of keeping Korean postpartum traditions, desire for professional Korean postpartum care, "Sanhoo-Joeri" postpartum support and social networking, normalization of PPD symptoms, family first for health seeking attitude and behavior, and stigma attached to mental health care. Clinical Implications: Nurses working with Korean women during postpartum can provide culturally competent care by assessing postpartum care needs, respecting cultural practices, and providing resources such as Korean postpartum care centers Sanhoo-Joeriwon, which can be found in major U.S. cities with large Korean communities (e.g., Los Angeles), and in-home postpartum care providers, Sanhoo-Joerisa. Nurses should be comfortable educating women about normal signs and symptoms of PPD and those requiring immediate medical follow-up. Abstract : Korean Americans are one of the six largest Asian American subgroups, representing 9% of the Asian American population in the United States, however they have not been well represented in studies of postpartum depression. In this study, Korean women who had immigrated to the United States were interviewed about their postpartum experience.